2017
DOI: 10.1007/s13197-017-2984-y
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional profile and molecular fingerprints of indigenous black jamun (Syzygium cumini L.) landraces

Abstract: The indigenous black jamun landraces ( L.), found in western Gujarat of Gir forest region (India), produced fruits with different size and shape. Fruit morphology like shape, volume, weight, length, girth were examined and black jamun categorized into six landraces viz., BJLR 1 (big fruit, > 11 g); BJLR 2 (medium to big fruit, 8-11 g); BJLR 3 (medium fruit, 6-8 g); BJLR 4 (medium to small fruit, 5-6 g); BJLR 5 (small fruit, 3-5 g) and BJLR 6 (very small fruit, < 3 g fruit weight). The landraces (BJLR 1 and 2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Our previous study Gajera et al [26,27] suggested that antidiabetic activity of fruit parts of black jamun landraces was positively correlated with free radical scavenging activity, nutraceuticals profile and individual phenolic constituents. Total phenols and individual phenolics are positively correlated with antidiabetic and antiradical activities but vary with different level of significances.…”
Section: Correlations Between Antidiabetic Antiradical and Phenolic Compoundsmentioning
confidence: 93%
“…Our previous study Gajera et al [26,27] suggested that antidiabetic activity of fruit parts of black jamun landraces was positively correlated with free radical scavenging activity, nutraceuticals profile and individual phenolic constituents. Total phenols and individual phenolics are positively correlated with antidiabetic and antiradical activities but vary with different level of significances.…”
Section: Correlations Between Antidiabetic Antiradical and Phenolic Compoundsmentioning
confidence: 93%
“…Carbohydrates are the main nutrient of the jamun seeds [Benherlal & Arumughan, 2007;Ghosh et al, 2017;Indrayan et al, 2005]. Among digestible carbohydrates, which provide the energy needed to support various metabolic processes in the human body, starch dominates with the content ranging from 23 g/100 g to 60 g/100 g dm of seed [Benherlal & Arumughan, 2007;Gajera et al, 2018]. The content of total soluble sugars is negligible -0.1-1.4 g/100 g [Gajera et al, 2018;Ghosh et al, 2017].…”
Section: Carbohydratesmentioning
confidence: 99%
“…India is ranked second, accounting for around 15.4% of total global production, or 13.5 million tonnes [https://www.agrifarming.in/jamun-farming]. Jamun fruits are small, usually oval-shaped with a pink purple to blue black colour when completely ripe, with a subtly sweet, astringent, and sour flavour, and a firm seed inside [Gajera et al, 2018;de Sousa Sabino et al, 2018;un Din et al, 2020]. At fully ripen stage, jamun pulp contains sugars (glucose, fructose), free amino acids, minerals (Na, K, Ca, Mn, Mg), dietary fiber, ascorbic acid, β-carotene, organic acids [Gajera et al, 2018;Seraglio et al, 2018], phenolic compounds (anthocyanins, flavonols, ellagotannins and gallotannins) [Faria et al, 2011;Lestario et al, 2017], volatile compounds (trans--ocimene, cis-ocimene, β-myrcene, and α-terpineol), and flavouring compounds (dihydrocarvyl acetate, geranyl butyrate, and terpinyl valerate) [Vijayanand et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of oxalic, gallic, tannic acids and other alkaloids creates one to feel such an astringency taste. The pulp and seeds are used for traditional medicine against diabetes, diarrhea, and ringworm infection also protect against radiation-induced sickness 32,[34][35][36][37] . It is very beneficial as it has anti-diabetic, cytoprotective, anticoagulant, analgesic and anti-inflammatory, anti-cancerous, anti-microbial, anti-oxidant, hypo-lipidemic, hepato-protective properties 35,38,39 .…”
Section: Jamun Powder Is Made From Sun-dried Jamun Seedsmentioning
confidence: 99%